2020
DOI: 10.3390/ijerph17176232
|View full text |Cite
|
Sign up to set email alerts
|

South Indian Cuisine with Low Glycemic Index Ingredients Reduces Cardiovascular Risk Factors in Subjects with Type 2 Diabetes

Abstract: Background: Inflammation is considered as a predictor of cardiovascular diseases in type 2 diabetes mellitus. No previous studies have investigated the effect of low glycemic index (LGI) recipes of South Indian cuisine on the risk factors of cardiovascular disease in patients with diabetes. Aim: The aim of this randomized controlled trial was to evaluate the improvement in cardiovascular risk factors and blood glucose control, in patients with type 2 diabetes, after intervention with recipes of Kerala cuisine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Of 188 reports reviewed in full, 161 were excluded based on eligibility criteria. A total of 27 reports containing data for 29 trial comparisons involving 1617 participants with diabetes were included in the final analyses 212223242627283031545556575859606162636465666768697071…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 188 reports reviewed in full, 161 were excluded based on eligibility criteria. A total of 27 reports containing data for 29 trial comparisons involving 1617 participants with diabetes were included in the final analyses 212223242627283031545556575859606162636465666768697071…”
Section: Resultsmentioning
confidence: 99%
“…Supplemental figures S17-S30 show influence analyses, in which systematic removal of individual trials altered the results. Removal of single trial comparisons resulted in changes in a gain of significance in the pooled effect estimate for the decrease in waist circumference26; loss of significance for the decrease in triglycerides22232627565771 and apoB,6268 although the direction of the pooled effect estimate still favoured low GI/GL diets; and partial explanation of the evidence of substantial heterogeneity for HbA 1c ,21 fasting glucose,212768 non-HDL-C,65 HDL-C,222763 apoB,71 waist circumference,26 and SBP and DBP 27…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of whole grains in preference to refined grains is known to have improved health benefits, with the broad range of benefits often attributed solely to the presence of dietary fiber [10,53]; however, other components, phytochemicals, fatty acids, amino acids, vitamins, and minerals are all likely to play a role. This review of 31 RCTs found that consumption of whole grain foods had a moderate effect on reducing inflammatory markers, with five of the possible 15 crossover studies [33,38,40,42,50], and seven of 16 parallel studies demonstrating statistically significant changes [23,[29][30][31][32]43,49]. Within the population groups studied, the reduction in markers was most often observed in obese and overweight populations, and among those with pre-existing conditions, compared with studies of healthy populations, although there were only two studies in this category.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were assessed against the predetermined criteria of the Cochrane RoB2 tool for randomized control and crossover trials [21]. Within Domain 1: Randomization Process, there were five studies with some concerns of bias [24,28,30,31,43], with the remaining studies (n = 26) with a low risk of bias. In Domain 2: Deviations from intended intervention, there was one study with a high risk of bias [22], one with some concern [31], and the remainder with a low risk of bias (n = 29).…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation